Penerapan Green Water System (GWS) terhadap Hatching Rate Telur Ikan Lele Sangkuriang (Clarias Gariepinus) - Rissa Amelia; Arif Supendi; Novita MZ (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Increasing catfish seed production sustainably is important to meet market needs. One effort to increase seed production is through the degree of egg hatching. This study aims to test the effectiveness of the application of the green water system on the success of hatching sangkuriang catfish eggs. The method used in this study was an experiment with two levels of treatment and 3 replications. The results of the study from the spawning of a pair of parents, obtained an average fertilization rate value produced in the GWS pond of 96.6% and the control pond 97.4%. In addition, the hatching rate showed a difference, with an average in the GWS pond of 90.6% while in the control pond 78.3%. The difference in the degree of egg hatching in the GWS pond can be associated with several factors, such as the availability of higher dissolved oxygen. Dissolved oxygen in the GWS pond is higher through the process of photosynthesis. Chlorophyceae is the most abundant phytoplankton found in the GWS hatching pond. Based on the research results, it can be concluded that the implementation of the Green Water System is effective in increasing the hatching of sangkuriang catfish eggs with an HR of 90.6%. This can be an alternative technology that is useful for cultivators to increase seed production.